Tuning Up Listening Skills: Unveiling the Impact of Busuu Application on Junior High School Students' Listening Proficiency - Utami, Aisyah Cucu; Astutik, Yuli (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
This study aims to examine the impact of the Busuu application on students' listening skills. This research uses a pre-experimental quantitative approach with a pre-test and post-test design in one group. This research specifically used eighth grade students at MTs Anwarul Maliki and was conducted in three stages: pretest, treatment, and posttest. Research findings show a significant improvement in students' listening skills in class VIII B before and after treatment with the Busuu application. This application has proven to be more effective than traditional methods, improving the practice and effectiveness of listening learning. The results of data analysis show an increase in students' average pre-test score from 34.44 to 64.44 from the average post-test score with the use of the Busuu application, making the process of learning listening skills easier and more practical. The results of this research can provide evidence to readers regarding the use of busuu which can affect junior high students' English listening abilities. This research implies that the Busuu application is more effective than traditional methods in improving listening skills. This provides empirical support for the use of technology in language learning, showing that technology-based methods can provide better results.